A novel high sensitivity UPLC-MS/MS method for the evaluation of bisphenol A leaching from dental materials - De Nys, Siemon (Sci Rep, 2018)
There is a growing necessity to acquire more profound knowledge on the quantity of eluates from resin-based dental materials, especially with regard to bisphenol A (BPA). The aim of the present study was to develop a highly sensitive method to characterize the short-term release of BPA in saliva with ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS), using an extraction step and additional derivatization of BPA with pyridine-3-sulfonyl chloride. Light-cured resin-based composites were incubated at 37 °C in 1 mL artificial saliva, which was refreshed daily for one week. The final protocol allows accurate quantification of very low levels of BPA in samples of artificial saliva (i.e. 1.10 pmol BPA/mL or 250 pg/mL). The daily BPA-release from dental composites, ranging from 1.10 to 7.46 pmol BPA/mL, was characterized over a period of 7 days. The highest total amount of BPA was released from Solitaire 2 (24.72 ± 2.86 pmol), followed by G-ænial Posterior (15.51 ± 0.88 pmol) and Filtek Supreme XTE (12.00 ± 1.31 pmol). In contrast, only trace amounts of BPA were released from Ceram.x Universal. This UPLC-MS/MS method might be used for clinical research focusing on the evaluation of the clinical relevance of BPA release from dental materials.